Handling Repeated Crimes (Residivist) of Motor Vehicle Theft (Case Study at Sukabumi District Police) - Nurpadilah, Siti Suci; Juhana, Ujuh (International Journal of Law Analytics, 2024)
The development of the times affects life in society which is marked by increasing crime in society. There are criminals who repeat crimes after the perpetrator is released from his criminal sentence or are known to be recidivists. The research method used is qualitative research, using an empirical legal approach which examines law which is conceptualized as real behavior, as an unwritten social phenomenon, which is experienced by everyone in social life.Research Methods In this research, the author used several research methods to complete this thesis. The first method used is the normative juridical method. Normative juridical is a legal research method carried out by examining library materials or mere secondary materials. The results of research into factors causing recidivism of motorbike theft in the jurisdiction of the Pelabuhan Ratu Police, Sukabumi Regency, namely educational factors, opportunity factors, lack of skills factors, and law enforcement factors. The recidivist modus operandi of motorbike theft in the jurisdiction of the Pelabuhan Ratu Police, Sukabumi Regency is in the form of using a T-lock, pushing the motorbike and hiding it in another place. Efforts to deal with recidivist motorbike theft in the jurisdiction of the Pelabuhan Ratu Police, Sukabumi Regency in the form of repressive and preventive efforts.